Type 2 Diabetes Mellitus and Pulmonary Function Impairment - Wagiran Wagiran; Barlie Brasila; Aditya Sardi; Sunarti Sunarti; Sohibun Sohibun; Rika Yuanita Pratama; Denny Saptono Fahrurodzi (Jurnal Ners, 2025)
Diabetes mellitus (DM) is a disease that can lead to complications in other organs, such as the lungs, which typically manifest after three years of DM onset. Mild symptoms often reduce public vigilance. Information and research on this topic are still rare. This study aims to determine the relationship between type 2 DM and pulmonary function disorders in individuals aged 40-65 years. This quantitative study employs a cross-sectional design. A total of 2,414 respondents were randomly selected. Cox regression analysis was used. The proportion of pulmonary function disorders in type 2 DM patients was 48.8%. A significant relationship was found, with a prevalence ratio of 1.99 (1.67-2.37; p=0.000) after controlling for age, sex, and smoking degree. Increasing awareness of pulmonary function testing in type 2 DM patients is an important consideration for preventing further complications